EFFECT OF COMPREHENSIVE OCULAR AND CERVICAL MUSCLE RE-EDUCATION PROGRAM (COCMRP) ON PAIN, DISABILITY AND QUALITY OF LIFE IN PATIENTS WITH NON-SPECIFIC NECK PAIN – A RANDOMIZED CONTROLLED TRIAL - Muskan Agrawal; Pradeep Borkar (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Background: Nonspecific neck pain is an increasingly frequent musculoskeletal condition in the middle-aged group. Recent research highlights sensorimotor control disturbances, head-eye movement control deficit in patients with chronic neck pain. The reason of the long-term neck pain is the incongruence between the sensorimotor conflict from the cortical network areas created by the gaze direction and the sensorimotor feedback. It is therefore possible to alleviate the neck pain by changing the gaze direction and adjusting the sensorimotor incongruence. The aim of the study was to find the effect of Comprehensive ocular and cervical muscle re-education program (COCMRP) on pain, disability and quality of life in patients with non-specific neck pain. Methodology: After designing the study Institutional Ethical Approval was taken. Consent was obtained from all the participants. 69 samples were screened based on eligibility criteria, 9 were excluded and were further divided into Group A (experimental group) and Group B (control group). Pre-assessment was done at Week 0. The experimental group received the Comprehensive ocular and cervical muscle re-education program for 3 session per week for 8 weeks, receiving total 24 sessions. The control group did their regular exercise program. Post-assessment was done at week Result: The Shapiro-Wilk test was used to assess the normality of data distribution. Analysis of variance (ANOVA) was used for comparison of mean at different time intervals. There were non-significant differences between the groups for disability and quality of life at Week 0. (p>0.05) There was a significant difference between the groups for pain, disability and quality of life balance at week 8 (p<0.05). Conclusion: The study concludes that Comprehensive ocular and cervical muscle re-education program is beneficial in reducing pain, disability and improving quality of life in patients with nonspecific neck pain